2007
DOI: 10.1021/jp0715474
|View full text |Cite
|
Sign up to set email alerts
|

Probing Methylene Blue Photocatalytic Degradation by Adsorbed Ethanol with In Situ IR

Abstract: The dynamic behavior of infrared (IR)-observable species during the methylene blue [i.e., MB, (CH 3 ) 2 N(C 6 H 3 )NS + (C 6 H 3 )N(CH 3 ) 2 Cl -] photocatalytic degradation (PCD) on TiO 2 has been investigated at 30°C. Exposure of MB/TiO 2 to UV illumination led to the scission of the N-CH 3 bond followed by breaking of the C-H and CdN bonds in the MB central aromatic ring and the side aromatic rings, indicating demethylation as the first step of the MB PCD. The bond breaking in the MB molecule and subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(78 citation statements)
references
References 52 publications
(108 reference statements)
6
72
0
Order By: Relevance
“…The positive intensity reveals the emergence of the intermediate species and inal products such as H 2 O at 1636 cm −1 (O-H bending vibration) and a sharper one at 3325 cm −1 (O-H stretching vibration), and CO 2 at 2201 cm −1 , whereas the negative intensity relects the scission of the special bonds in the CB molecules [43]. This is in line with previous nano-photocatalytic degradation and oxidation studies [44][45][46]. The results demonstrated that not only the chromophore section of the CB molecules was destroyed totally, but also the structure of CB molecules was mineralized to CO 2 and H 2 O by the nano-photocatalytic degradation in the presence of GQDs.…”
Section: Photocatalytic Degradation Behavior Of Celestine Bluesupporting
confidence: 87%
“…The positive intensity reveals the emergence of the intermediate species and inal products such as H 2 O at 1636 cm −1 (O-H bending vibration) and a sharper one at 3325 cm −1 (O-H stretching vibration), and CO 2 at 2201 cm −1 , whereas the negative intensity relects the scission of the special bonds in the CB molecules [43]. This is in line with previous nano-photocatalytic degradation and oxidation studies [44][45][46]. The results demonstrated that not only the chromophore section of the CB molecules was destroyed totally, but also the structure of CB molecules was mineralized to CO 2 and H 2 O by the nano-photocatalytic degradation in the presence of GQDs.…”
Section: Photocatalytic Degradation Behavior Of Celestine Bluesupporting
confidence: 87%
“…Increasing the exposure period increased in the absorption spectra at wave numbers of around 1000 cm −1 , 1388 cm −1 , 1600 cm −1 and 3450 cm −1 . The same peaks were identified by Yu and Chuang (2007). Increasing the exposure time caused the increase in absorption of wave numbers 3450 cm -1 , indicating the increase in concentration of hydroxyl radical OH in the solution MB.…”
Section: Discussionsupporting
confidence: 58%
“…Recent studies on photocatalytic oxidation of ethanol on TiO 2 demonstrated that the simultaneous measurement of IR intensity of photogenerated electrons and adsorbed species during the reaction allow determination of the photocatalytic reaction pathway and identification of the role of electron and hole in the reaction [106,107]. Figure 7b shows that photocatalytic oxidation of ethanol on the H 2 O ad -deficient TiO 2 (i.e., TiO 2 with low H 2 O content) surface produced adsorbed acetic acid CH 3 COOH ad ð Þ CH 3 COO À ad and built up photogenerated electrons.…”
Section: Photocatalystmentioning
confidence: 99%